PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPS SMA NEGERI 2 PAYAKUMBUH - Eka Fitri (Jurnal Edukasi dan Penelitian Matematika, 2022)
Understanding mathematical concepts is a fundamental skill that all students must master. However, in SMA Negeri 2 Payakumbuh, class XI IPS students' understanding of these concepts is still subpar, and they haven't taken an active part in their education. Think Pair Square (TPSq) cooperative learning is the answer to these issues. This study set out to examine the differences between students in class XI at IPS SMA Negeri 2 Payakumbuh who were taught using a cooperative learning model of the TPSq type and those who were taught using more traditional methods in terms of their grasp of mathematical subjects. This study uses an experimental and descriptive design with a non-equivalent posttest-only control group. P-value is determined through data analysis. 0. 000 obtained H0 is rejected, meaning that students understanding of mathematical concepts taught by the TPSq type of cooperative learning model is better than that taught by conventional learning. Keywords– Understanding Mathematical Concepts, Cooperative learning model TPSq Type, Conventional Learning